Hubungan Konsumsi Kopi dan Perilaku Merokok dengan Tekanan Darah pada Mahasiswa Laki-Laki Fakultas Sains dan Teknologi di Universitas PGRI Yogyakarta - Jhon Raiber Sinaga; Adhila Fayasari (PT Bukuloka Literasi Bangsa, 2026)
Hypertension is a noncommunicable disease with a continuously increasing prevalence, including among young adults. Coffee consumption and smoking behavior are lifestyle factors suspected to be associated with increased blood pressure. This study aimed to analyze the association of coffee consumption and smoking behavior with blood pressure among male students at the Faculty of Science and Technology, Universitas PGRI Yogyakarta. This study employed an analytical observational design with a cross-sectional approach involving 46 respondents selected using purposive sampling. Data on coffee consumption and smoking behavior were collected using questionnaires, while blood pressure was measured using a digital sphygmomanometer. Most respondents were categorized as moderate coffee drinkers (71.7%), light-to-moderate smokers (84.8%), and had normal blood pressure (52.2%). Data were analyzed using the Spearman correlation test and Fisher’s exact test. The results showed no significant association between coffee consumption (p = 0.774) or smoking behavior (p = 0.418) and blood pressure. It was concluded that coffee consumption and smoking behavior were not significantly associated with blood pressure in this population. Keywords: coffee consumption, smoking behavior, blood pressure, hypertension, students